The contributions of resting-state functional-MRI studies to our understanding of male patients with obstructive sleep apnea: a systematic review - Yu, Ruoxi; Li, Yan; Zhao, Kangqing; Fan, Fangfang (Frontiers in Neurology, 2025)
ObjectivesObstructive sleep apnea (OSA) is a condition marked by the recurrent partial or complete obstruction of the upper airway during sleep. This leads to intermittent pauses in breathing, fragmented sleep, and frequent awakenings throughout the night. Many of these symptoms are believed to be linked to brain damage; however, the fundamental neurological processes underlying these impairments remain largely unknown. This study investigates resting-state functional MRI (rs-fMRI) findings in male patients with OSA to better understand the specific mechanisms associated with this condition in this demographic.MethodsThe search was conducted in the PubMed and Google Scholar databases, encompassing literature from their inception to July 2024. Studies were identified based on predetermined inclusion and exclusion criteria and were evaluated by two independent reviewers.ResultsA total of 16 eligible original rs-fMRI studies on male patients with OSA were included in this review. The findings indicate that patients with OSA exhibit alterations in resting-state brain activity. These neural changes may help explain the effects of OSA on emotion, cognition, and quality of life. Additionally, these findings could be used in the future to evaluate treatment outcomes.ConclusionThis study highlights significant changes in local brain activities, interested region related functional connectivity, and whole-brain functional connectivity networks in patients with OSA. These findings offer valuable insights into the neural alterations at the core of OSA and may serve as potential biomarkers for diagnosis and intervention.